Intellectual synthesis in mentorship determines success in academic careers - Jean F. Liénard (Nature Portfolio, 2018)
While successful mentors tend to train successful students in academic career, it’s unclear how mentorship determines chances of a success in a trainee. Here, Liénard and colleagues analyze approximately 20 K mentor/trainee relationships in life sciences, and find that success of trainees is associated with an intellectual synthesis between their mentors’ research.